(untitled) (Philological Studies, 2019)
According to intertextuality, memory is an image of presenting a culture into literature. A culture is nothing else but the other face of history. History represents the past and memory is an eternal present or a contemporary past. Memory nourishes itself with the vivid and active remembrances that encourage us to act. Every remembrance helps us see the contemporaneousness that gets sense, i.e., the real place between the past and the future. The motive for this text is the memory of the Moravian mission, i.e., the 1150 jubilee of that mission and the importance of that mission for descendents of the big Slavonic tribe. A real confirmation for a cross game of memory and the writer’s imagination is the novel The Alphabet for the Disobedient (1994) by Macedonian novelist Venko Andonovski. In this novel, through the story situated in 863 CE, in the monastery Polichrono at Mount Olympus, Anatolia Eyalet, Andonovski leads a covered philosophical debate in which the questions are pointed directly to the reader; at the same time, he asks the reader how much he knows about himself, about his history, the Bible, mythology, folklore.